Application of Point Counting Petrography for Provenance Determination; Implication for Tectonic Development from the Semilir Formation, Gunung Kidul - Krisnabudhi, Alfathony; Rizky, Aga; Farisan, Ardhan; Isnani, Desi Kumala; Widada, Sugeng; Ardine, Joseph Emmanuel; Aiman, Muhammad Naufal; Tony, Brian; Mardiati, Dani (Journal of Applied Sciences, Management and Engineering Technology, 2025)
The provenance sediments have been analyzed to reveal tectonic development during the Semilir Formation deposition in the Southern Mountain of Yogyakarta area, using essential samples from field observation, petrography analysis, and the point counting method. Outcrop and sampling at two observation points revealed distinct lithological features, including sandstone and siltstone with mudclast structures and slump structures interbedded with siderite. Petrographic analysis using the point-counting method determined the mineral composition of four samples: 1A, 1B, 2A, and 2B. Samples 1A and 1B were categorized as Lithic Wacke, 2A Feldspathic Wacke, and 2B Lithic Wacke. Provenance analysis, crucial for understanding the sedimentary history and reconstructing the geological events preceding sediment deposition, identified that the sandstones in the Ngoro-oro region predominantly fall into the magmatic arc category. Hence, based on our analysis, the tectonic development during Semilir Fm deposition is linked with the convergence event of the first subduction on southern Java, which had huge volcanic influences and slope morphology common in volcanic areas. The findings of this study contribute to a deeper understanding of the tectonosedimentary processes and geological history of the Ngoro-oro region. The integrated approach of petrographic and provenance analyses provides a comprehensive view of the sedimentary rocks formation and evolution, enriching the geological knowledge of the area.